ANALISIS TEKS, KONTEKS SITUASI, DAN KOTEKS PADA VIDEO “KITA MARAH, DAN INI PERINGATAN DARURATNYA” - Gitayani, Ni Nyoman Tri; Melani, Ni Putu Dian Angga (Prosiding Seminar Nasional Bahasa Ibu; Vol 2 No 1 (2025): Prosiding Seminar Nasional Bahasa Ibu 2024/2025, 2025)
Back in August 2024, Indonesia experienced a political polemic related to the Constitutional Court's decision ahead of the 2024 simultaneous regional head elections. The polemics had been widely broadcasted in the form of videos through YouTube. One of the videos was uploaded in the form of a narrative reported by Najwa Shihab and could even gain high public attention and inflict many different public interpretations. Based on this phenomenon, this research was conducted that aims at analyzing the text, the context of the situation, and co-text contained in Najwa Shihab's video transcription. The research object was a video uploaded by Najwa Shihab entitled “ Kita Marah, dan Ini Peringatan Daruratnya” . The data were analyzed using qualitative methods and the theory of the context of the situation by Holmes. The results of the analysis showed that the transcription of the video “ Kita Marah, dan Ini Peringatan Daruratnya ” belonged to the editorial text. There were four features of the context of the situation, namely participants (Najwa Shihab and Indonesian society), time setting (Tuesday), topic (politics), and function (informative and persuasive). In addition, there was also the use of co-text that supported the unity of the text in the form of the word usage ‘ini’, ‘itu’ , and the clitic '-nya'. This research can be used as a reference and help the readers to comprehend the text, the context of the situation, and co-text elements in the digital text form.